A dhesion analysis via a tumor vasculature-like microfluidic device identifies CD8+ T cells with enhanced tumor homing to improve cell therapy - Camila P. Camargo; Abir K. Muhuri; Yunus Alapan; Lauren F. Sestito; Megha Khosla; Margaret P. Manspeaker; Aubrey S. Smith; Chrystal M. Paulos; Susan N. Thomas (Cell Reports, 2023)
Summary: CD8+ T cell recruitment to the tumor microenvironment is critical for the success of adoptive cell therapy (ACT). Unfortunately, only a small fraction of transferred cells home to solid tumors. Adhesive ligand-receptor interactions have been implicated in CD8+ T cell homing; however, there is a lack of understanding of how CD8+ T cells interact with tumor vasculature-expressed adhesive ligands under the influence of hemodynamic flow. Here, the capacity of CD8+ T cells to home to melanomas is modeled ex vivo using an engineered microfluidic device that recapitulates the hemodynamic microenvironment of the tumor vasculature. Adoptively transferred CD8+ T cells with enhanced adhesion in flow in vitro and tumor homing in vivo improve tumor control by ACT in combination with immune checkpoint blockade. These results show that engineered microfluidic devices can model the microenvironment of the tumor vasculature to identify subsets of T cells with enhanced tumor infiltrating capabilities, a key limitation in ACT.